Entrepreneurial Finance in Emerging Markets
LII, 390 p. 21 illus.
Keywords: This book presents a wide range of tools and techniques used in entrepreneurial finance in emerging markets. Among them, venture capital is perhaps the best known, understood, and researched mode of entrepreneurial finance. However, a significant focus of the book is dedicated to other modes of entrepreneurial finance such as ‘bootstrapping,’ angel financing, bank financing, and other alternative means of financing, which could include government assistance programs, business incubation, technology parks, or family financing. In addition, the book highlights how new and innovative financial technologies (comprised of software, business processes, and other modern technologies), known under the term of FinTech, may support, enable, and enhance the provision of different modes of entrepreneurial finance in emerging markets. The book also discusses entrepreneurial finance in emerging markets in the context of women entrepreneurs. A comprehensive analysis of entrepreneurial finance in emerging market countries, this book will appeal to academics, researchers, and students of entrepreneurial finance, venture capital and private equity, entrepreneurship, and international business. .